Disturbed spermatogenic signaling in pituitary adenylate cyclase activating polypeptide-deficient mice. Issue 2 (February 2018) - Reglodi, D; Cseh, S; Somoskoi, B; Fulop, B D; Szentleleky, E; Szegeczki, V; Kovacs, A; Varga, A; Kiss, P; Hashimoto, H; Tamas, A; Bardosi, A; et al.
Abstract : PACAP is a neuropeptide with diverse functions in various organs, including reproductive system. It is present in the testis in high concentrations, and in addition to the stage-specific expression within the seminiferous tubules, PACAP affects spermatogenesis and the functions of Leydig and Sertoli cells. Mice lacking endogenous PACAP show reduced fertility, but the possibility of abnormalities in spermatogenic signaling has not yet been investigated. Therefore, we performed a detailed morphological analysis of spermatozoa, sperm motility and investigated signaling pathways that play a role during spermatogenesis in knockout mice. No significant alterations were found in testicular morphology or motility of sperm in homozygous and heterozygous PACAP-deficient mice in spite of the moderately increased number of severely damaged sperms. However, we found robust changes in mRNA and/or protein expression of several factors that play an important role in spermatogenesis. Protein kinase A expression was markedly reduced, while downstream phospho-ERK and p38 were elevated in knockout animals. Expression of major transcription factors, such as Sox9 and phospho-Sox9, was decreased, while that of Sox10, as a redundant factor, was increased in PACAP-deficient mice. The reduced phospho-Sox9 expression was partly due to increased expression and activity of phosphatase PP2A in knockout mice. Targets of Sox transcription factors, such as collagen type IV, were reduced in knockout mice. In summary, our results show that lack of PACAP leads to disturbed signaling in spermatogenesis, which could be a factor responsible for reduced fertility in PACAP knockout mice, and further support the role of PACAP in reproduction.